2019
DOI: 10.1101/532283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyclin E expression is associated with high levels of replication stress in triple-negative breast cancer

Abstract: Replication stress entails the improper progression of DNA replication. In cancer cells, including breast cancer cells, an important cause of replication stress is oncogene activation. Importantly, tumors with high levels of replication stress may have different clinical behavior, and high levels of replication stress appear to be a vulnerability of cancer cells, which may be therapeutically targeted by novel molecularly targeted agents.Unfortunately, data on replication stress is largely based on experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Amplification and overexpression of oncogenes such as Cyclin E (CCNE1) [87][88][89], Ras [90], Myc [91,92] and CDC25A [88] have also been linked with increased replication stress and enhanced sensitivity to ATRi, whereas genetic screens have identified a range of additional cancer-associated ATRi-related synthetic lethal effects including those with ARID1A [93], RNASEH2A/ RNASEH2B [94], POLE3/POLE4 [95], APOBEC3A/ APOBEC3B [96] amongst others [97][98][99][100][101][102][103][104][105]. To what extent these pre-clinical observations translate to clinically meaningful biomarkers remains to be assessed in clinical trials [75].…”
Section: Resistance To Atr Inhibitorsmentioning
confidence: 99%
“…Amplification and overexpression of oncogenes such as Cyclin E (CCNE1) [87][88][89], Ras [90], Myc [91,92] and CDC25A [88] have also been linked with increased replication stress and enhanced sensitivity to ATRi, whereas genetic screens have identified a range of additional cancer-associated ATRi-related synthetic lethal effects including those with ARID1A [93], RNASEH2A/ RNASEH2B [94], POLE3/POLE4 [95], APOBEC3A/ APOBEC3B [96] amongst others [97][98][99][100][101][102][103][104][105]. To what extent these pre-clinical observations translate to clinically meaningful biomarkers remains to be assessed in clinical trials [75].…”
Section: Resistance To Atr Inhibitorsmentioning
confidence: 99%
“…33 Moreover, prospective studies could help clarify whether the observed association between CCNE1 expression and response to CDK4/6 inhibitors is a true treatment interaction effect or whether CCNE1 only identifies a subset of patients who have poor prognosis overall, regardless of treatment, as earlier studies (not in the context of CDK4/6 inhibitor treatment) suggested. 54,55 For clinical practice, it is important to consider that even patients with high levels of CCNE1 derived benefit from the addition of palbociclib to fulvestrant in PALOMA-3, and therefore, this biomarker should be carefully implemented to not exclude patients who could benefit from this therapy. Thymidine kinase 1 (TK1), a cell cycle-dependent cytosolic enzyme, plays an important role in the synthesis of DNA and cellular proliferation.…”
Section: Biology Of Cdksmentioning
confidence: 99%